From natural resource to subject of rights: a thematic analysis of the evolution of the legal protection of rivers - Cano, Carlos Alberto Gómez; Polania, Libardo Ramón; Castilllo, Verenice Sánchez (Journal of Ecohumanism, 2024)
The objective was to analyze the legal, theoretical, and ontological transformations present in the scientific literature on river protection between 2018 and 2023. A critical narrative review with qualitative thematic analysis was conducted. Based on two Scopus searches, 966 unique records were integrated, and a final corpus of 17 articles was purposively selected for their relevance, conceptual diversity, and explanatory power. The analysis identified four interdependent dimensions: the expansion of the river's legal status, the incorporation of relational and biocultural foundations, the institutionalization of representation mechanisms, and the persistence of implementation gaps. Recognizing rivers as subjects of rights did not replace their treatment as resources or public goods; instead, it gave rise to hybrid legal configurations. The effectiveness of these innovations depended on the clarity of obligations, the legitimacy and autonomy of guardians, substantive community participation, and the institutional capacity to transform the material causes of degradation. Riverine legal personhood holds greater potential when it integrates status, relational foundations, representation, and implementation. Isolated declarations increase visibility and access to justice but prove insufficient to guarantee effective ecological protection.